Multi-Antigenic Recombinant Subunit Vaccine Against Lawsonia Intracellularis: The Etiological Agent of Porcine Proliferative Enteropathy - Cortez-San Martin, M (Elsevier Ltd, 2019)
Proliferative enteropathy, caused by Lawsonia intracellularis, represents a threat for swine industry. Current vaccines are effective but difficult to obtain and scaled up, because of demanding bacterial culture conditions. In this work, a subunit vaccine candidate against L. intracellularis was developed and its efficacy was evaluated in vivo, alone or co-formulated with pig recombinant IFN-α. The vaccine formulation contains three chimeric antigens: two outer membrane proteins and a secreted one, which were engineered by adding T epitopes using bioinformatics tools. After simultaneously expressing the three antigens in E. coli, its immunogenicity was tested in mice and pigs. Antigens co-formulated with porcine IFN-α were also assayed in the last species. Immune response was assessed by ELISA and qPCR, and histopathological studies of intestinal epithelial tissue were performed after challenge. Mice and pigs showed an increased IgG response against chimeric antigens. Particularly, there were significant differences in the antibody response when porcine IFN-α was co-administrated with L. intracellularis antigens. Besides, mRNAs from il12 and cd4 marker were detected during the first week after immunization of pigs, suggesting a Th1-type cellular immune response. The significant enhancement of oas2 gene expression indicates the effect exerted by porcine IFN-α. Post-mortem histopathological analysis post-challenge revealed damage only into epithelial cells of the gastrointestinal tract from animals of the negative control group. Injuries were related to atrophy of the intestinal villi, where a decrease of globet cells and a greater migration of lymphocytes were observed. Overall, our results demonstrated that the vaccine candidate elicited significant humoral and cellular immune responses. Besides, histopathological analysis suggested that vaccinated animals were protected against experimental L. intracellularis infection. This research constitutes a step forward to the generation of the first recombinant chimeric vaccine against L. intracellularis, representing a faster, easier and cost effective approach to counteract the porcine proliferative enteropathy. © 2019 Elsevier Ltd